2022
DOI: 10.3390/d14090773
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomic Delimitation of the Monostromatic Green Algal Genera Monostroma Thuret 1854 and Gayralia Vinogradova 1969 (Ulotrichales, Chlorophyta)

Abstract: The genera Monostroma and Gayralia belong to the order of monostromatic green algae; however, their taxonomic delimitation remains controversial at the genus level. This study attempts to address this issue through the combined analysis of the morphology and nuclear-encoded Internal Transcribed Spacer region sequences of monostromatic green algal samples collected in the South China Sea. Our phylogenetic data revealed that the monostromatic specimens were separated into the M. nitidum clade, G. brasiliensis cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…( 2013 ) and Cui et al. ( 2022 ), the ITS sequences of G. oxysperma and G. brasiliensis exhibited genetic differences of at least 0.3 and 0.2, respectively. Pellizzari advocated for the retention of the genus Gayralia by proposing a new Brazilian species, G. brasiliensis .…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…( 2013 ) and Cui et al. ( 2022 ), the ITS sequences of G. oxysperma and G. brasiliensis exhibited genetic differences of at least 0.3 and 0.2, respectively. Pellizzari advocated for the retention of the genus Gayralia by proposing a new Brazilian species, G. brasiliensis .…”
Section: Discussionmentioning
confidence: 83%
“…An earlier study by our group analyzed the external morphological features and ITSs sequences of MGA from various locations along the coast of Guangdong, China (Cui et al., 2022 ). The results of the phylogenetic analysis revealed that MGA could be categorized into three branches: Monostroma nitidum , Gayralia brasiliensis , and Monostroma sp.…”
Section: Introductionmentioning
confidence: 99%
“…strain BPC-108 under controlled conditions and propagation of gametophytes similar to those of U. mutabilis. Finally, our study did not participate in the controversial taxonomic reclassification of Monostroma (Cui et al 2022).…”
Section: Limitations Of the Studymentioning
confidence: 99%